Characteristic analysis and fault‐tolerant control of modular multilevel converters under sub‐module faults. (28th October 2015) - Li, Tan; Zhao, Chengyong
Summary: This paper analyzes the operation characteristics of the modular multilevel converter when the arms are asymmetrical with different sub‐module number caused by sub‐module faults. The research reveals the problems caused by asymmetrical arms, including the asymmetrical capacitor voltages, the asymmetrical direct current (dc) components of the arm currents, the asymmetrical circulating currents, the dc current fluctuation, and the voltage offset at the dc or alternating current (ac) side. Then, it is demonstrated by the theoretical analysis that the series of problems can be solved by rebalancing the fundamental frequency components of the upper arm voltage and the lower arm voltage. Therefore, a fault‐tolerant control strategy is proposed by introducing a fundamental frequency resonant controller to the traditional second‐order frequency proportional resonant circulating current controller. Besides, the research shows that the coordination of the proposed control strategy and the negative sequence current suppressing control can keep the output voltages of the three phases balanced. A 201‐level modular multilevel converter–high‐voltage direct current time‐domain simulation model is established based on PSCAD/EMTDC, and the simulation studies confirm the efficiency of the proposed controller under balanced and unbalanced ac grid conditions. Copyright © 2015 John Wiley & Sons, Ltd.